Economic Crisis and Growth in Vote Share for Extreme Left and Extreme Right Parties - Jitka Doležalová (Review of Economic Perspectives, 2015)
Economic hardship fuels worries about a possible higher share of extremist parties in European legislature and executive. The article examines whether the recent economic recession resulted in growth in electoral support for the extreme right and the extreme left in parliamentary elections. The empirical analysis includes a set of 23 EU member states and observes the period from 1995 to 2012. A supplementary aim is to determine to what degree this phenomenon has a greater impact on countries that were forced to resort to IMF financial intervention. The analysis reveals that decline in GDP and growth in unemployment helped increase electoral support for extremist parties in the EU countries. Simultaneously, their share in the lower house representation grew. In these cases, the increase in support was primarily for extreme left parties. The inflation rate did not have any significant impact on growth in vote share for extremist parties. An increased vote share for extremist parties was more apparent in countries in receipt of an IMF loan.
Keywords: 330